A Qualitative Study of drivers behaviour for practicing safety riding - Merdiaty, Netty; Abdillah, Rijal; Nainee, Sarvarubini (JURNAL SPIRITS, 2025)
Safety riding in traffic results from a complex interaction of various factors, one of which is driver behavior, influenced by cognitive aspects such as knowledge of traffic signs. This knowledge is an important indicator of prosocial behavior in the context of driving. This study explores riders’ knowledge of traffic signs and the disciplines contributing to the likelihood of traffic accidents. Non-compliance with traffic regulations is often the basic trigger for accidents, which not only have material impacts but also pose a risk of physical injury and death. This research uses a qualitative approach with a phenomenological methods to explore a person’s awareness and compliance in traffic, and how safe riding behavior develops. Two research subjects and two informants were selected as study participants through the purposive sampling technique to obtain relevant data. The research results show the subject’s understanding of safety riding, their awareness of traffic, and their level of compliance with traffic regulations. Although police officers have tried to implement the principle of safety riding, in reality, many people have still not internalized safe driving behavior. Hence, traffic accidents remain a worrying problem.